Effect of bevacizumab against cystic components of brain tumors. (9th September 2019) - Yamasaki, Fumiyuki; Kolakshyapati, Manish; Takano, Motoki; Yonezawa, Ushio; Nishibuchi, Ikuno; Imano, Nobuki; Taguchi, Akira; Onishi, Shumpei; Amatya, Vishwa Jeet; Takeshima, Yukio; Nagata, Yasushi; Kurisu, Kaoru; et al.
Abstract: Background: Bevacizumab improves symptoms via reducing the peritumoral edema and/or normalizing blood brain barrier, and occasionally via reducing the tumor size. However, the effect against active cystic components has not been documented yet. Materials and Methods: Between 2008 and 2018, 139 patients with primary or metastatic brain tumors were treated with bevacizumab (BEV) in our institution. The images and symptoms before and after administration of BEV were examined, and changes in size of cysts were evaluated as follows: CR (complete disappearance), PR (reduction by ≥50%), MR (reduction by ≥25%), SD (size change <25%), PD (increase by ≥25%). The effect of BEV on tumor itself was determined according to Response Assessment in Neuro‐Oncology criteria. Results: Of the 139 patients, 21 (15.1%) had cystic components. The best responses of cysts to BEV treatment were as follows: CR 6, PR 7, MR 4, SD 4. The group of patients with progressively increasing cysts prior to BEV treatment had significant cyst size reduction compared to stable cyst size groups, at initial imaging after BEV (mean 62.6% vs 22.5%, P = .0055) and at best response timing (mean 76.3% vs 32.8%, P = .0050). Patients with cysts showed significant improvement in symptoms after the treatment with BEV compared to patients without cysts ( P = .0033). However, response rate was not different between patients with or without cysts. Overall survival after starting BEV was not different between glioblastoma patients with or without cysts. Conclusion: Bevacizumab is effective against progressively increasing cysts. Although cysts reduction effect and tumor response and/or overall survival are independent, BEV may be effective in patients who are symptomatic due to cyst enlargement. Abstract : Patients with cyst showed significant improvement in symptoms after the treatment with bevacizumab (BEV) compared to patients without cyst. Bevacizumab is effective against progressively increasing cysts. Although cyst reduction effect and tumor response and/or overall survival are independent, BEV may be effective in patients who are symptomatic due to cystic enlargement.